Assignment 4

course Mth 163

assignment #004004.

Precalculus I

09-15-2008

......!!!!!!!!...................................

15:29:32

`questionNumber 40000

`q001. Note that this assignment has 4 questions

If f(x) = x^2 + 4, then find the values of the following: f(3), f(7) and f(-5). Plot the corresponding points on a graph of y = f(x) vs. x. Give a good description of your graph.

......!!!!!!!!...................................

RESPONSE -->

f(x) = x^2 + 4

f(3) = 3^2 + 4

9+4

f(3)=13

(3,13)

f(7) = 7^2 + 4

49+4

f(7)=53

(7, 53)

f(-5) = -5^2 + 4

25+4

f(-5)=29

(-5,29)

I plotted the points (3,13) (7, 53) (-5,29) and got parabola in the top two quadrants.

confidence assessment: 2

.................................................

......!!!!!!!!...................................

15:29:49

`questionNumber 40000

f(x) = x^2 + 4. To find f(3) we replace x by 3 to obtain

f(3) = 3^2 + 4 = 9 + 4 = 13.

Similarly we have

f(7) = 7^2 + 4 = 49 + 4 = 53 and

f(-5) = (-5)^2 + 9 = 25 + 4 = 29.

Graphing f(x) vs. x we will plot the points (3, 13), (7, 53), (-5, 29). The graph of f(x) vs. x will be a parabola passing through these points, since f(x) is seen to be a quadratic function, with a = 1, b = 0 and c = 4.

The x coordinate of the vertex is seen to be -b/(2 a) = -0/(2*1) = 0. The y coordinate of the vertex will therefore be f(0) = 0 ^ 2 + 4 = 0 + 4 = 4. Moving along the graph one unit to the right or left of the vertex (0,4) we arrive at the points (1,5) and (-1,5) on the way to the three points we just graphed.

......!!!!!!!!...................................

RESPONSE -->

ok I see

self critique assessment: 2

.................................................

......!!!!!!!!...................................

15:38:22

`questionNumber 40000

`q002. If f(x) = x^2 + 4, then give the symbolic expression for each of the following: f(a), f(x+2), f(x+h), f(x+h)-f(x) and [ f(x+h) - f(x) ] / h. Expand and/or simplify these expressions as appropriate.

......!!!!!!!!...................................

RESPONSE -->

f(x) = x^2 + 4

f(a) = a^2 + 4

f(x+2) = x+2^2 + 4 simplify

f(x+2) = (x^2+4x + 4)+4

f(x+2) = x^2+4x +8

f(x+h) = (x+h)^2+4

f(x+h) = (x+h)(x+h)+4

f(x+h) = x^2+2xh+h^2+4

f(x+h)-fx = x^2+2xh+h^2+4-x^2+4 use equations already found

f(x+h)-fx =2xh+h^2

[f(x+h)-fx]/h= use last answer and divide by h

2xh+h^2/h=2x+h

confidence assessment: 2

.................................................

......!!!!!!!!...................................

15:38:34

`questionNumber 40000

If f(x) = x^2 + 4, then the expression f(a) is obtained by replacing x with a:

f(a) = a^2 + 4.

Similarly to find f(x+2) we replace x with x + 2:

f(x+2) = (x + 2)^2 + 4, which we might expand to get (x^2 + 4 x + 4) + 4 or x^2 + 4 x + 8.

To find f(x+h) we replace x with x + h to obtain

f(x+h) = (x + h)^2 + 4 = x^2 + 2 h x + h^2 + 4.

To find f(x+h) - f(x) we use the expressions we found for f(x) and f(x+h):

f(x+h) - f(x) = [ x^2 + 2 h x + h^2 + 4 ] - [ x^2 + 4 ] = x^2 + 2 h x + 4 + h^2 - x^2 - 4 = 2 h x + h^2.

To find [ f(x+h) - f(x) ] / h we can use the expressions we just obtained to see that

[ f(x+h) - f(x) ] / h = [ x^2 + 2 h x + h^2 + 4 - ( x^2 + 4) ] / h = (2 h x + h^2) / h = 2 x + h.

......!!!!!!!!...................................

RESPONSE -->

I get it.

self critique assessment: 2

.................................................

......!!!!!!!!...................................

15:41:54

`questionNumber 40000

`q003. If f(x) = 5x + 7, then give the symbolic expression for each of the following: f(x1), f(x2), [ f(x2) - f(x1) ] / ( x2 - x1 ). Note that x1 and x2 stand for subscripted variables (x with subscript 1 and x with subscript 2), not for x * 1 and x * 2. x1 and x2 are simply names for two different values of x. If you aren't clear on what this means please ask the instructor.

......!!!!!!!!...................................

RESPONSE -->

f(x) = 5x + 7

f(x1) = 5(x1) + 7

f(x2) = 5(x2) + 7

[f(x2)-f(x1)]/ (x2-x1)= [5(x2+7)-5(x1+7)]/(x2-x1)= 5x2-5x1/x2-x1

Not sure if this is right, sort of guessed.

confidence assessment: 2

.................................................

......!!!!!!!!...................................

15:42:09

`questionNumber 40000

Replacing x by the specified quantities we obtain the following:

f(x1) = 5 * x1 + 7,

f(x2) = 5 * x2 + 7,

[ f(x2) - f(x1) ] / ( x2 - x1) = [ 5 * x2 + 7 - ( 5 * x1 + 7) ] / ( x2 - x1) = [ 5 x2 + 7 - 5 x1 - 7 ] / (x2 - x1) = (5 x2 - 5 x1) / ( x2 - x1).

We can factor 5 out of the numerator to obtain

5 ( x2 - x1 ) / ( x2 - x1 ) = 5.

......!!!!!!!!...................................

RESPONSE -->

ok i see

self critique assessment: 2

.................................................

......!!!!!!!!...................................

15:43:18

`questionNumber 40000

`q004. If f(x) = 5x + 7, then for what value of x is f(x) equal to -3?

......!!!!!!!!...................................

RESPONSE -->

fx) = 5x + 7

-3 = 5x + 7

-3+-7=5x

-10/5=5x/5

-2=x

confidence assessment: 2

.................................................

......!!!!!!!!...................................

15:43:31

`questionNumber 40000

If f(x) is equal to -3 then we right f(x) = -3, which we translate into the equation

5x + 7 = -3.

We easily solve this equation (subtract 7 from both sides then divide both sides by 5) to obtain x = -2.

......!!!!!!!!...................................

RESPONSE -->

ok i see

self critique assessment: 2

.................................................

&#This looks good. Let me know if you have any questions. &#

&#Let me know if you have questions. &#